2018
DOI: 10.1039/c8ta09491h
|View full text |Cite|
|
Sign up to set email alerts
|

Interplay between H2O and CO2 coadsorption and space-charge on Y-doped BaZrO3 surfaces

Abstract: Crucial role of coadsorption, surface defects and subsurface space-charge on the surface chemistry of oxides is demonstrated by first-principles calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Polfus et al have shown that the space-charge layer forming within the BZY sample affects the defect concentration near the surface, changing the affinity for species adsorption, including dissociative adsorption. 30 According to them, dissociative water incorporation in barium zirconate is more favorable than molecular adsorption. This is supported by the strongly negative enthalpies of hydration at low coverage.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polfus et al have shown that the space-charge layer forming within the BZY sample affects the defect concentration near the surface, changing the affinity for species adsorption, including dissociative adsorption. 30 According to them, dissociative water incorporation in barium zirconate is more favorable than molecular adsorption. This is supported by the strongly negative enthalpies of hydration at low coverage.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…At the highest water uptake, this process starts to be limited by proton diffusivity through the bulk. Polfus et al have shown that the space-charge layer forming within the BZY sample affects the defect concentration near the surface, changing the affinity for species adsorption, including dissociative adsorption . According to them, dissociative water incorporation in barium zirconate is more favorable than molecular adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…47 A recent study on CO 2 and H 2 O coadsorption has shown preferential adsorption of H 2 O on BZY and indicated that the presence of H 2 O prevents the formation of a carbonate overlayer on BZY surfaces. 48 For applications with high CO 2 partial pressures due reforming of hydrocarbons, the presence of steam may therefore limit the BaCO 3 formation and the associated degradation processes. Further degradation studies should therefore take into account both CO 2 and H 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on grain boundary segregation, another study substantiated the space-charge formation due to defect segregation [218]. Furthermore, co-adsorption of H 2 O and CO 2 study along with the space-charge attribute of BZO have shown that space-charge formation and adsorbate interaction contribute to de ning defect concentrations [219]. For a speci c study on defect chemistry and solubility of perovskites, DFT calculations have played an instrumental role.…”
Section: Theoretical Studies On Bzo Proton Conductormentioning
confidence: 97%